Chasing Tone: How Rob Turner and EMG Revolutionized the Guitar’s Sound - Reilly, Jim (Rowman & Littlefield Publishers, 2023)
Prince, Pink Floyd, Metallica, Toto, James Taylor, Keith Richards—these stars and thousands of others all owe a debt of gratitude to Rob Turner who revolutionized the electric guitar and bass. Chasing Tone tells Rob Turner’s story from humble beginnings rewiring his father’s transistor radio components to founding EMG and, finally, to the world’s largest concert stages. Jim Reilly provides a wealth of fascinating insights by weaving together many exclusive interviews with top artists and colleagues, including James Hetfield, Kirk Hammett, and Robert Trujillo of Metallica; legendary session musician Leland Sklar; Vernon Reid of Living Colour; Victor Wooten; Béla Fleck; Nili Brosh; Jim Root of Slipknot; and guitar builders Mike McGuire and John Carruthers. Along the way, Reilly not only sheds light on the history of the electric guitar and bass and how EMG pickups forever altered their course but also explores the elusive relationship between builder and creator, showing how these artists found their sound. This book takes a deep dive into the creative process while providing a history of popular music told from a side of the stage previously underexplored.